Risk factors and surgical site infection in trauma-orthopedic surgeries - Silva, Edilane Neves da; Silva, Renata Kelly dos Santos e; Carvalho, Simone Barroso de; Façanha, Dilene Maria de Araújo; Carvalho, Rhanna Emanuela Fontelene Lima de; Pereira, Francisco Gilberto Fernandes (Revista Cuidarte, 2021)
Introduction: Infection of the Surgical Site occupies the third position among infections acquired in health services, representing an important public health problem, present in about 15% of those found in hospitalized patients, and one of the types of most likely for this event are trauma-orthopedic surgies. Objective: To verify the association between risk factors and the presence of Surgical Site Infection in traumato-orthopedic surgeries. Materials and methods: Prospective descriptive, quantitative study, conducted between August and October 2017 with 84 patients. The data regarding the patient, the procedure and the signs of Surgical Site Infections, found on the third and tenth postoperative days, were collected using a form. Results: Of the studied variables, they behaved as risk factors for Surgical Site Infection: smoking, diabetes and age over 50 years. Age was the main risk factor related to the patient, present in 31, 36.9% of cases. Pain, edema and hyperemia were the most prevalent signs of infection. Discussion and conclusions: The risk factors related to the patient are more relevant in the association with infection of the surgical site compared to those related to the procedure.How to cite this article: Silva, Edilane Neves da; Silva, Renata Kelly dos Santos e; Carvalho, Simone Barroso de; Façanha, Dilene Maria de Araújo; Carvalho, Rhanna Emanuela Fontelene Lima de; Pereira, Francisco Gilberto Fernandes. Fatores de risco para infecção de sítio cirúrgico em cirurgias traumato-ortopédicas. Revista Cuidarte. 2021;12(2):e1292. http://dx.doi.org/10.15649/cuidarte.1292
Keywords: Risk factors; Cross Infection; Surgical Wound; Orthopedics; Perioperative Nursing